A Paper On Renewal Function - Gençoğlu, M.t., S.özçelik (My University, 1997)
In this paper, after giving the defination of integral equation and renewal function
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Renewal Fonctions